Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1104/pp.120.3.913
|View full text |Cite
|
Sign up to set email alerts
|

A Plastidial Lysophosphatidic Acid Acyltransferase from Oilseed Rape1

Abstract: The biosynthesis of phosphatidic acid, a key intermediate in the biosynthesis of lipids, is controlled by lysophosphatidic acid (LPA, or 1-acyl-glycerol-3-P) acyltransferase (LPAAT, EC 2.3.1.51). We have isolated a cDNA encoding a novel LPAAT by functional complementation of the Escherichia coli mutant plsC with an immature embryo cDNA library of oilseed rape (Brassica napus). Transformation of the acyltransferase-deficient E. coli strain JC201 with the cDNA sequence BAT2 alleviated the temperature-sensitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 32 publications
(26 reference statements)
2
43
0
5
Order By: Relevance
“…75). Indeed, we identified 2-lysophosphatidate acyltransferase (76), an enzyme catalyzing the transfer of 16:0 (from 16:0-ACP) to the sn-2 position of lysophosphatidic acid, leading to the synthesis of phosphatidic acid, the precursor for chloroplast glycerolipids. MGD1, one of the three Arabidopsis monogalactosyldiacylglycerol (MGDG) synthases, the last committed step in MGDG biosynthesis, was identified in our previous study on spinach (7).…”
Section: The Protein Import Machinery Of Chloroplast Envelopementioning
confidence: 99%
“…75). Indeed, we identified 2-lysophosphatidate acyltransferase (76), an enzyme catalyzing the transfer of 16:0 (from 16:0-ACP) to the sn-2 position of lysophosphatidic acid, leading to the synthesis of phosphatidic acid, the precursor for chloroplast glycerolipids. MGD1, one of the three Arabidopsis monogalactosyldiacylglycerol (MGDG) synthases, the last committed step in MGDG biosynthesis, was identified in our previous study on spinach (7).…”
Section: The Protein Import Machinery Of Chloroplast Envelopementioning
confidence: 99%
“…Evolution of Higher-Plant LPAAT Bourgis et al (1999) suggested that the alignment of the deduced amino acid sequences has the same orthologous relationship in sll1848 and plastidial LPAAT from Brassica napus (BAT2). This idea is confirmed by the observation that both LPAAT1/ATS2 from Arabidopsis and sll1848 from Synechocystis sp PCC6803 show a preference for 16:0 ACP (and 16:0 CoA in vitro).…”
Section: Evolution Of Cyanobacterial Lpaatmentioning
confidence: 99%
“…A fascinating aspect of glycerolipid biosynthesis is that there often exists an asymmetric distribution of fatty acid (FA) molecules between the sn-1 and sn-2 positions: Saturated and monounsaturated FAs are normally found at sn-1, whereas polyunsaturated fatty acids (PUFAs) are enriched at sn-2. Pioneering work on plant acyltransferases has shown that GPATs and LPAATs are not only stereo-specific with regard to acylation of the glycerol backbone but also selective in terms of acyl-CoA donors (Griffiths et al, 1985;Ohlrogge and Browse, 1995;Oo and Huang, 1989;Bourgis et al, 1999;Kim and Huang, 2004;Kim et al, 2005). Therefore, the substrate specificity of the acyltransferases of the Kennedy pathway is one of the determining factors of the composition of glycerolipid molecules.…”
Section: Introductionmentioning
confidence: 99%